Interactions of nanomaterials with ion channels and related mechanisms. (4th September 2019) - Yin, Suhan; Liu, Jia; Kang, Yiyuan; Lin, Yuqing; Li, Dongjian; Shao, Longquan
Abstract : The pharmacological potential of nanotechnology, especially in drug delivery and bioengineering, has developed rapidly in recent decades. Ion channels, which are easily targeted by external agents, such as nanomaterials (NMs) and synthetic drugs, due to their unique structures, have attracted increasing attention in the fields of nanotechnology and pharmacology for the treatment of ion channel‐related diseases. NMs have significant effects on ion channels, and these effects are manifested in many ways, including changes in ion currents, kinetic characteristics and channel distribution. Subsequently, intracellular ion homeostasis, signalling pathways, and intracellular ion stores are affected, leading to the initiation of a range of biological processes. However, the effect of the interactions of NMs with ion channels is an interesting topic that remains obscure. In this review, we have summarized the recent research progress on the direct and indirect interactions between NMs and ion channels and discussed the related molecular mechanisms, which are crucial to the further development of ion channel‐related nanotechnological applications.